Translation suppression underlies the restrained COVID-19 mRNA vaccine response in the high-risk immunocompromised group - Kim, Kangsan; Narasimhan, Madhusudhanan; Mahimainathan, Lenin; Zhang, Ray; Araj, Ellen; Kim, Elizabeth; Tharpe, William; Greenberg, Benjamin M.; Greenberg, David E.; Li, Quan-Zhen; Cheng, Chi-An; Sarode, Ravi; et al. (Frontiers in Immunology, 2022)
Background: Immunocompromised (IC) patients show diminished immune response to COVID-19 mRNA vaccines (Co-mV). To date, there is no ‘empirical’ evidence to link the perturbation of translation, a rate-limiting step for mRNA vaccine efficiency (VE), to the dampened response of Co-mV. Materials and methods: Impact of immunosuppressants (ISs), tacrolimus (T), mycophenolate (M), rapamycin/sirolimus (S), and their combinations on Pfizer Co-mV translation were determined by the Spike (Sp) protein expression following Co-mV transfection in HEK293 cells. In vivo impact of ISs on SARS-CoV-2 spike specific antigen (SpAg) and associated antibody levels (IgGSp) in serum were assessed in Balb/c mice after two doses (2D) of the Pfizer vaccine. Spike Ag and IgGSp levels were assessed in 259 IC patients and 50 healthy controls (HC) who received 2D of Pfizer or Moderna Co-mV as well as in 67 immunosuppressed solid organ transplant (SOT) patients and 843 non-transplanted (NT) subjects following three doses (3D) of Co-mV. Higher Co-mV concentrations and transient drug holidays were evaluated. Results: We observed significantly lower IgGSP response in IC patients (p<0.0001) compared to their matched controls in 2D and 3D Co-mV groups. IC patients on M or S showed a profound dampening of IgGSP response relative to those that were not on these drugs. M and S when used individually or in combination, significantly attenuated the Co-mV-induced Sp expression, whereas T did not exert significant influence. Sirolimus combo pretreatment in vivo significantly attenuated the Co-mV induced IgMSp and IgGSp production, which correlated with a decreasing trend in the early levels (after day 1) of Co-mV induced Sp immunogen levels. Neither higher Co-mV concentrations (6μg) nor withholding S for 1-day could overcome the inhibition of Sp protein levels. Interestingly, 3-days S holiday or using T alone rescued Sp levels in vitro. Conclusions: This is the first study to demonstrate that ISs, sirolimus and mycophenolate inhibited Co-mV-induced Sp protein synthesis via translation repression. Selective use of tacrolimus or drug holiday of sirolimus can be a potential means to rescue translation-dependent Sp protein production. These findings lay a strong foundation for guiding future studies aimed at improving Co-mV responses in high-risk IC patients.